Remarkable response to a novel ATR inhibitor in a patient with poorly differentiated neuroendocrine carcinoma. (2018) - Saito, Yoshihito David; Li, Zaibo; Lustberg, Maryam; Grenade, Cassandra; Wesolowski, Robert
Abstract: M6620 (formerly known as VX-970) is a potent inhibitor of ataxia telangiectasia and Rad3-related protein (ATR), a serine/threonine-specific protein kinase involved in activation of checkpoint signaling and promotion of cell cycle arrest in response to DNA damage (inhibition constant [Ki] <300 pM, IC50 of 20 nM). ATR inhibition enhances the cytotoxic effect of DNA damaging drugs and infrared radiation (IR) in many cancer cell lines and primary human tumors. M6620 is currently under investigation in early-phase clinical trials for the treatment of a number of malignancies. Below, we report a case of a patient with metastatic prostate cancer with clonal evolution to poorly differentiated large cell neuroendocrine carcinoma who developed an exceptional response to treatment with M6620 and cisplatin on a phase I trial VX12-970-001 (NCT02157792: An Open-Label, First-in-Human Study of the Safety, Tolerability, and Pharmacokinetics of VX-970 in Combination With Cytotoxic Chemotherapy) with over 20 months of non-CNS progression free survival. We will discuss the mechanism of action of M6620, rationale for enrolling the patient in this trial and hypothesize the reasons for this exceptional response. Highlights: Alterations to components of the DNA damage response (DDR) pathway may promote carcinogenesis in a number of cancers. ATR plays a critical role in the DDR and its inhibition may lead to synthetic lethality in tumors dependent on intact ATR function. M6620 is an emerging, potent ATR inhibitor. Here we report a case of a patient with metastatic, hormone-refractory prostate cancer with neuroendocrine differentiation with a somatic BRCA2 mutation and alteration in ATR gene (duplication of exons 1–3) who had a long non-CNS progression free survival while treated with M6620. We will discuss the mechanism of action of M6620 and literature that supports testing ATR inhibitors in patients with cancer.